Analisis Penerapan Green Economy dalam Manajemen Koperasi Sekolah untuk Meningkatkan Kesadaran Lingkungan Siswa: Studi Pustaka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Increasingly complex environmental issues demand a shift in economic approaches moving beyond a singular focus on profit toward long-term sustainability. The concept of a green economy has emerged as a highly relevant framework for integration into the educational sphere, particularly through contextual learning. This study aims to analyze how the application of green economy principles within school cooperatives can contribute to enhancing students’ environmental awareness. The methodology employed is a qualitative approach using descriptive analysis based on literature reviews and observations of contextual learning practices. The findings indicate that integrating a green economy into school cooperative activities facilitates a more meaningful learning experience. Students do not merely grasp economic concepts theoretically but are also able to correlate them with environmental impacts in their daily lives. Furthermore, direct student involvement in sustainability-based economic activities fosters pro-environmental attitudes and more responsible decision-making skills. This aligns with the concept of sustainable education, which emphasizes the importance of instilling eco-friendly values and behaviors from an early age. Consequently, school cooperatives can be developed as effective pedagogical tools to support the sustainable cultivation of ecological awareness among students.